Isolation of a Pigment-producing Strain of Staphylococcus kloosii from the Respiratory Tree of Holothuria (Mertensiothuria) leucospilota (Brandt 1835) from Malaysian Waters - Kamarul Rahim Kamarudin; Nurziana Ngah; Tengku Haziyamin Tengku Abdul Hamid; Deny Susanti (Tropical Life Sciences Research, 2013)
Staphylococcus kloosii, an orange pigment-producing bacterium, was isolated from the respiratory tree of Holothuria (Mertensiothuria) leucospilota (Brandt 1835) from Teluk Nipah, Pangkor Island, Perak, Malaysia. This report is the first documentation of this Gram-positive strain, referred to as Strain 68 in Malaysia. A partial 16S ribosomal RNA gene sequence of the mesophilic strain has been registered with GenBank (National Center for Biotechnology Information, US National Library of Medicine) with accession number JX102547. Phylogenetic analysis using the neighbour-joining method further supported the identification of Strain 68 as S. kloosii. The circular strain produced orange pigments on tryptone glucose yeast extract agar (TGYEA) and in nutrient broth (NB) at approximately pH 7. The visible spectra of ethanolic and methanolic pigment extracts of the bacterial strain were considered identical with ?max at 426, 447 and 475 nm and ?max at 426, 445 and 473 nm, respectively. Both visible spectra resemble the visible spectra of lutein, which is a commercial carotenoid; however, further analyses are required to confirm the identity of this pigment. The methanolic extracts of the intracellular pigments comprised at least three pigment compounds: an orange pigment compound (major compound), a yellow pigment compound (the least polar) and a pink pigment compound (the most polar). These findings are the first documentation of the pigment composition of S. kloosii as no such record could be found to date. Staphylococcus kloosii , sejenis bakteria yang menghasilkan pigmen berwarna oren, telah dipencilkan dari pohon respirasi Holothuria (Mertensiothuria) leucospilota (Brandt 1835) dari Teluk Nipah, Pulau Pangkor, Perak, Malaysia. Laporan ini merupakan dokumentasi pertama tentang strain Gram-positif ini yang dikenali sebagai Strain 68 di Malaysia. Satu jujukan separa gen 16S ribosom RNA strain mesofilik tersebut telah didaftarkan dengan GenBank (National Center for Biotechnology Information, US National Library of Medicine) dengan nombor akses JX102547. Analisis-analisis filogenetik menggunakan kaedah hubungkait jiran serta kaedah persamaan maksimum seterusnya menyokong pengecaman strain tersebut iaitu Strain 68 sebagai S. kloosii. Strain berbentuk bulat ini menghasilkan pigmen-pigmen keorenan di atas agar ekstrak tripton glukosa yis (TGYEA) dan di dalam bubur nutrisi (NB) pada pH lebih kurang 7. Spektrumspektrum nampak ekstrak-ekstrak ethanol dan methanol pigmen strain bakteria tersebut dianggap serupa dengan ?max pada 426, 447 dan 475 nm dan ?max pada 426, 445 dan 473 nm, masing-masing. Kedua-dua spektrum nampak kelihatan menyamai spektrumspektrum nampak lutein, karotenoid yang bernilai komersil; walau bagaimanapun, analisisanalisis lanjutan adalah diperlukan untuk mengesahkan identitinya. Dari segi komposisi pigmen, ekstrak methanol pigmen intrasel tersebut terdiri daripada sekurang-kurangnya tiga bahan pigmen iaitu bahan pigmen oren (bahan utama), bahan pigmen kuning (paling tidak berpolar) dan bahan pigmen merah jambu (paling berpolar). Menariknya, penemuanpenemuan ini juga merupakan dokumentasi pertama tentang komposisi pigmen strain S. kloosii memandangkan tiada rekod berkenaan dapat dijumpai sehingga kini.